Taguchi Experiment Design for DES K2CO3-Glycerol Performance in RBDPO Transesterification - Susila Arita; Leily Nurul Komariah; Winny Andalia; Fitri Hadiah; Cindi Ramayanti (Emerging Science Journal, 2023)
Biodiesel production using novel glycerol and potassium carbonate-based catalysts has not been developed under the Taguchi technique. This study aims to determine the most influential parameter in biodiesel production from refined bleach-deodorized palm oil (RBDPO) using DES K2CO3-Glycerol as the novel catalyst. The raw material was subjected to transesterification at the desired reaction parameters estimated by the orthogonal 16-run (L16) approach with 2 levels and 4 factors of the Taguchi technique. Signal-to-noise ratio (SNR) and ANOVA were used to confirm the predicted value. From the results, the catalyst is the most influential variable in the TG value of biodiesel, placed in the first rank of the influence factor. Biodiesel production with a minimum total glycerol value (0.210%) using DES K2CO3-Glycerol as a catalyst is most optimally produced at 95 °C for 4 h and 400 rpm using 30 wt% methanol and 4 wt% catalysts achieved by the Taguchi technique. The biodiesel obtained from RBDPO complies with the required international standards. Doi: 10.28991/ESJ-2023-07-03-018 Full Text: PDF